The Soul According to Ibn Sina - Yousef Al-Hadi Misbah Aoun (Journal of Scientific and Human Dimensions, 2026)
The question of the soul is one of the most significant philosophical issues that has occupied human thought throughout history, as it is closely tied to human existence and the meaning of life. This issue received particular attention from Ibn Sina, who examined it from various intellectual and philosophical perspectives, attempting to define its essence, its function, its relationship to the body, and the resulting metaphysical and epistemological problems. This study seeks to analyze the concept of the soul in Ibn Sina’s philosophy, highlighting its philosophical dimensions and situating it within the broader Islamic philosophical tradition, while also attempting to approach it through a contemporary lens that connects Ibn Sina’s ideas with the findings of modern psychology.
Keywords: Soul; Philosophical issues; Human existence; Ibn Sina; Islamic philosophical tradition